Current management of hypertension in chronic kidney disease - Kittinuntaponchai, Komson; Sukkha, Sayamon (Journal of Medicine and Health Sciences, 2021)
A gradual increase in chronic kidney disease (CKD) patients worldwide has been a challenge in terms of health care professionals after optimizing therapy for CKD. One of the key strategies of CKD management is to delay the progression of kidney disease, as well as reducing the risk factors for cardiovascular disease (CVD). Hypertension is a significant factor for both CKD progression and CVD. Therefore, taking care of blood pressure should be emphasized to all CKD patients. The proper measurement of blood pressure (BP) has been important for the diagnosis, evaluation, and follow-up on patients with hypertension. The Office Blood Pressure Monitoring (OBPM) has been widely used in clinical practice. Ambulatory blood pressure monitoring (ABPM) and home blood pressure monitoring (HBPM) have been an alternative BP measurement for selected patients. As many guidelines have set OBPM as a target for blood pressure, patients who measured their blood pressure by ABPM or HBPM, which should be reconsidered to individually determine optimal blood pressure. Several published guidelines on hypertension in CKD have been updated with considering the recent evidence from clinical studies. The target of blood pressure depended on various factors, such as the staging of CKD, albuminuria levels and other comorbidities. Almost all of the guidelines for CKD patients have been consistent with a target BP of 130/80 mmHg or lower. Furthermore, renin angiotensin aldosterone system (RAAS) blockers, including ACEIs/ARBs have been recommended in a wide range of patients with kidney diseases, particularly in those with albuminuria. Although acute kidney injury and hyperkalemia should be warranted in patients taking ACEIs/ARBs, other potential factors of those adverse effects should be intensively excluded before reducing the dose or discontinuing the drugs. Therefore, recommending CEIs/ARBs to CKD to patients who tended to benefit from blocking RAAS mechanisms should be encouraged. The selection of other anti-hypertensive medications should be considered based on the comorbidities of the students, adverse effects, important drug interactions, and clinical outcomes from CKD studies.